Refugee Health During the Covid-19 Pandemic: A Review of Global Policy Responses - Lupieri S (Dove Medical Press, 2021)
Sigrid Lupieri Department of Politics and International Studies, Centre of Development Studies, University of Cambridge, Cambridge, UKCorrespondence: Sigrid Lupieri Email sml48@cam.ac.ukAbstract: Refugees and displaced persons have been severely affected by the Covid-19 pandemic. Yet findings from this narrative review reveal that the health needs of refugees have been largely neglected within global healthcare responses. Such gaps include: (1) responding to the needs of refugees in camps and detention centers; (2) providing adequate public health information; (3) providing access to healthcare and mental health services; (4) and including refugees as decision-makers within health responses. More research is urgently needed to investigate why these gaps exists and to provide recommendations for improving the inclusiveness of healthcare policies during a pandemic.Keywords: refugees, Covid-19, pandemic, healthcare, global policy, review